Pengaruh Influencer, Online Customer Review, dan Viral Marketing terhadap Keputusan Pembelian Produk Skincare Skintific di Kota Semarang - Oktavina, Radifajna Annis; Amron, Amron; Safitri, Maria; Oktavia, Vicky (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to examine the influence of influencers, online customer reviews, and viral marketing on purchasing decisions for Skintific skincare products in Semarang. The approach used was quantitative with a survey method, where data was obtained by distributing questionnaires to respondents who had knowledge or experience with the product. Furthermore, the data was analyzed using Partial Least Squares (PLS) to identify the relationship and level of influence between the research variables. The results showed that all three variables had a positive and significant influence on purchasing decisions, with online customer reviews emerging as the strongest factor in driving consumer choice. This indicates that reviews shared by other users can increase trust, provide an overview of product quality, and help consumers reduce risk before making a purchase. Furthermore, the presence of influencers and the widespread dissemination of information through viral marketing also strengthened purchasing interest by providing greater exposure to the product. Overall, these findings emphasize the importance of utilizing an integrated digital marketing strategy oriented towards consumer information needs. By optimizing these three aspects, companies have the opportunity to increase purchasing tendencies, strengthen brand positioning, and face increasingly competitive market competition.